Science Education in South Africa for the 21st century: Mutualism between Knowledge Domains - Botha, Marie Louise (South African Journal of Higher Education, 2016)
“Science has assumed an important role in the contemporary economy”, especially in the 21st century (Watters and Watters 2007). It also is a well-known fact that the quality of teaching and the teachers teaching science have a significant impact on the quality of learning. Science is a challenging subject; therefore the work of the educators and teachers involved in science education can also be very challenging, taking into account the varieties of knowledge required for teaching complex and abstract science concepts. Science education and teaching rely upon more than just science content as a school subject and topic-specific knowledge, instructional strategies and assessments (Lankford 2010). Teachers and educators of science need to understand science as a discipline, including the understanding of the nature of science and the integration of the various knowledge domains. The argument for mutualistic possibilities among these knowledge domains for “better” science education in the 21st century is investigated. This paper reports on a theoretical study in which a pool of concepts and principles were examined to provide an overview of the potential mutualism of a variety of knowledges that a successful and effective science teacher should acquire/have. Keywords: Science teaching, knowledge domains, mutualism